In vivo fluorescence correlation spectroscopy analyses of FMBP‐1, a silkworm transcription factor. Issue 2 (27th January 2016) - Tsutsumi, Motosuke; Muto, Hideki; Myoba, Shohei; Kimoto, Mai; Kitamura, Akira; Kamiya, Masakatsu; Kikukawa, Takashi; Takiya, Shigeharu; Demura, Makoto; Kawano, Keiichi; Kinjo, Masataka; Aizawa, Tomoyasu
Abstract : Fibroin modulator‐binding protein 1 (FMBP‐1) is a silkworm transcription factor that has a unique DNA‐binding domain called the one score and three amino acid peptide repeat (STPR). Here we used fluorescence correlation spectroscopy (FCS) to analyze the diffusion properties of an enhanced green fluorescent protein‐tagged FMBP‐1 protein (EGFP‐FMBP‐1) expressed in posterior silk gland (PSG) cells of Bombyx mori at the same developmental stage as natural FMBP‐1 expression. EGFP‐FMBP‐1 clearly localized to cell nuclei. From the FCS analyses, we identified an immobile DNA‐bound component and three discernible diffusion components. We also used FCS to observe the movements of wild‐type and mutant EGFP‐FMBP‐1 proteins in HeLa cells, a simpler experimental system. Based on previous in vitro observation, we also introduced a single amino acid substitution in order to suppress stable FMBP‐1‐DNA binding; specifically, we replaced the ninth Arg in the third repeat within the STPR domain with Ala. This mutation completely disrupted the slowest diffusion component as well as the immobile component. The diffusion properties of other FMBP‐1 mutants (e.g. mutants with N‐terminal or C‐terminal truncations) were also analyzed. Based on our observations, we suggest that the four identifiable movements might correspond to four distinct FMBP‐1 states: (a) diffusion of free protein, (b) and (c) two types of transient interactions between FMBP‐1 and chromosomal DNA, and (d) stable binding of FMBP‐1 to chromosomal DNA.